ANALISIS DUKUNGAN SOSIAL TERHADAP IDE BUNUH DIRI PADA REMAJA - Nurul Amiroh, Siti; Layalia Alyan, Wazna; Wijaya Abdul Rozak, Rama (Lafadz Jaya Publisher, 2024)
This research delineates the worrisome phenomenon of suicidal ideation among adolescents, particularly students, which is on the rise. This issue poses serious challenges to mental well-being and public health. The objective of this study is to investigate suicidal ideation among adolescents, focusing on the impact of insufficient social support as a contributing factor. A total of 101 respondents aged 18-24 participated in the study, utilizing qualitative descriptive methods and questionnaires as data collection instruments. The results indicate that a significant portion of respondents experiences suicidal ideation, with a high belief in the role of family support in reducing the risk of such thoughts. The complexity of social relationships, including a lack of support from friends and the repercussions of losing a partner, also plays a crucial role in suicidal ideation among adolescents. This research provides a foundation for an in-depth understanding of the factors influencing suicidal ideation and encourages more effective prevention efforts in the future. It contributes significantly to prevention by informing strategies with a specific emphasis on enhancing social support to reduce the prevalence of suicidal ideation and improve the overall mental well-being of adolescents.